Prevalence and Risk Factors of Denture Induced Stomatitis in Denture Wearers Attending Khanzad Dental Teaching Center in Erbil city - Dler Hidayat, Darya; Fakhree Alzubaidee , Ali (Diyala Journal of Medicine, 2023)
Background: Denture induced stomatitis often referred to as denture sore mouth and prosthetic stomatitis, denotes inflammation of the oral mucosa, particularly the palatal mucosa that are in close contact with the denture base. Objective: To evaluate the prevalence and risk factors of denture induced stomatitis in complete denture wearers attending Khanzad Teaching Dental Center. Patients and Methods: This study included one hundred consecutive upper denture wearers from prosthetic department in Khanzad Teaching Dental Center , the age range of the patients was 39-85 years .Different factors such as age, gender, denture age ,wearing time and hematinic parameters investigated and recorded .The diagnosis of denture stomatitis was done by clinical examination .The data entered and analyzes by (SPSS software version 25). Results: The prevalence of denture stomatitis was 20%. Non significant relashionship in the prevalence of denture stomatitis with age, gender, denture age, wearing time , type of denture and heamtinic deficiency. Conclusion: Because denture stomatitis is the most prevalent inflammatory reaction that affects denture wearers and is typically asymptomatic, it is better to schedule a routine dental check for them to allow early detection of any abnormalities to treat it and the choice of treatment depends on the cause of change. in many denture wearers the removal of traumatic as well as maintaining good oral hygiene and hygiene of dentures produce positive outcomes.